2017
DOI: 10.1093/brain/awx351
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning and metaplasticity in striatal neurons: relevance for Parkinson’s disease

Abstract: Nigro-striatal dopamine transmission is central to a wide range of neuronal functions, including skill learning, which is disrupted in several pathologies such as Parkinson's disease. The synaptic plasticity mechanisms, by which initial motor learning is stored for long time periods in striatal neurons, to then be gradually optimized upon subsequent training, remain unexplored. Addressing this issue is crucial to identify the synaptic and molecular mechanisms involved in striatal-dependent learning impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 56 publications
5
68
1
1
Order By: Relevance
“…Similar results were observed that human α-syn (h-α-syn) overexpression caused signi cant loss of dopaminergic neurons in the SNc (Fig. 7c) [52], reduction of TH and DAT protein levels in the SNc (Fig. 7d) and STR ( Supplementary Fig.17c), and these changes were markedly rescued by celastrol administration.…”
Section: The Effects Of Celastrol Are Mediated By Nrf2-nlrp3-caspase1supporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were observed that human α-syn (h-α-syn) overexpression caused signi cant loss of dopaminergic neurons in the SNc (Fig. 7c) [52], reduction of TH and DAT protein levels in the SNc (Fig. 7d) and STR ( Supplementary Fig.17c), and these changes were markedly rescued by celastrol administration.…”
Section: The Effects Of Celastrol Are Mediated By Nrf2-nlrp3-caspase1supporting
confidence: 83%
“…Recombinant AAVs (serotype 2 genome packaged in serotype 9 capsid) were used for the expression of human wild-type α-syn, GFP driven by the human synapsin-1 promoter and enhanced using a woodchuck hepatitis virus posttranscriptional regulatory element (WPRE) [51,52].…”
Section: Gait Testmentioning
confidence: 99%
“…Notably, however, mice were very slow to acquire lever pressing for D2 stimulation, the frequency of lever pressing was very low, and these mice pressed the laserpaired lever just as often as the inactive lever. A more recent study showed that D1 but not D2 receptors in the DLS mediate LTP during early rotarod learning in mice (Giordano et al, 2018).…”
Section: Basal Ganglia Contributions To Movement and Instrumental Leamentioning
confidence: 98%
“…These findings led to the hypothesis that local cholinergic neurons could be substituting for extrinsic glutamate following cortical ablations . Current work has explored similar ideas and the local plasticity of MSN firing has been found to be much greater than previously thought in the brain slice preparation from typical tissue as well as after alteration in brain connectivity or physiology (Giordano et al, 2018). Furthermore, recent work has pinpointed significant contributions of acetylcholine interneurons influencing thalamostriatal activity and found applications to better understand the neuropathology of Parkinson's disease (Li & Dauer, 2019;Tanimura, Du, Kondapalli, Wokosin, & Surmeier, 2019).…”
Section: Effec Ts Of Corti C Al Damag E On S Tr I Ata L Ac Ti V It Ymentioning
confidence: 85%